Transnational cinematic and popular music icons : Lena Horne, Dorothy Dandridge, and Queen Latifah, 1917-2017 - Lefkovitz, Aaron E. (Lexington Books, 2017)
"This book explores the films and popular music of Lena Horne, Dorothy Dandridge, and Queen Latifah, connecting each performer to female black-transnational histories and nonwhite female performers' representational struggles"--